1991
DOI: 10.1159/000163617
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Antigen Sites on Cells by Flow Cytometry

Abstract: We evaluated a cytofluorometric method for determining the number of antigens expressed on the cell surface of human lymphocytes. Using beads that have a known number of binding sites for mouse immunoglobulin and monoclonal antibodies specific for various antigens on human lymphocytes, we found that this system is quite reproducible, reliable and technically easy to perform. The greatest source of variation in expression of cell surface antigens is interdonor variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…First, except for the works of Lanzavecchia's group, 12,13 the possibility of even partial modulation of the level of expression of CD4 on T cells is not considered, even in the most recent papers on the subject. 7,8,22 One of these recent papers actually assumes absolute constancy of the numbers of CD4 molecules on T cells and uses this constant as a calibration gauge for estimation of the numbers of CD38 molecules. 8 Second, in healthy young subjects (being studied for the normal values of the CD4 expression), the percentages of CD4 lo cells are usually low (not exceeding 10% to 15% of all CD4 ϩ cells) and are seen in cytometric histograms mostly in the form of an inconspicuous shoulder at the main CD4 ϩ population.…”
Section: Discussionmentioning
confidence: 99%
“…First, except for the works of Lanzavecchia's group, 12,13 the possibility of even partial modulation of the level of expression of CD4 on T cells is not considered, even in the most recent papers on the subject. 7,8,22 One of these recent papers actually assumes absolute constancy of the numbers of CD4 molecules on T cells and uses this constant as a calibration gauge for estimation of the numbers of CD38 molecules. 8 Second, in healthy young subjects (being studied for the normal values of the CD4 expression), the percentages of CD4 lo cells are usually low (not exceeding 10% to 15% of all CD4 ϩ cells) and are seen in cytometric histograms mostly in the form of an inconspicuous shoulder at the main CD4 ϩ population.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil populations were identified with forward and right angle light scatter, and the fluorescence emission of 10 4 events/sample was recorded as mean channel number on a logarithmic scale. To calculate the number of receptors per cell, the mean channel number of each cell population was transformed into antibody binding sites per cell with Quantum Simply Cellular microbeads as previously described (15,49). The number of antibody binding sites corresponding to the isotopic immunoglobulin was subtracted from each cell sample.…”
Section: Methodsmentioning
confidence: 99%
“…However, as adhesion relies not only on the presence of CAMs, but also on their level of expression, 4,14 we quantified their level of expression using a flow cytometric methodology. 24 Our results demonstrated that the expression of CAMs in B cell NHL varied depending on the subtype as defined by the REAL classification, 25 with each subtype showing a unique pattern of expression for the five CAMs tested. Overall, the level of CAM expression was highest in high grade NHL, ie the most activated malignant cells.…”
Section: Introductionmentioning
confidence: 60%
“…The diagnosis was confirmed by immunological, histological and cytogenetic analysis (data not shown). NHL were classified according to the REAL classification: 25 24 small lymphocytic lymphoma (SLL), 15 mantle cell lymphoma (MCL), 39 follicular lymphoma (FL), four lymphoplasmacytoid lymphoma (LPL), 31 diffuse large cell lymphoma (DLCL) including 22 centroblastic (DLCL-CB) and nine immunoblastic (DLCL-IB) lymphoma. SLL, MCL, FL and LPL are considered as low or intermediate grade NHL, whereas DLCL-CB and DLCL-IB are high grade NHL.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation